Complete viral protein coding genes NS1 and VP1 sequences and phylogenetic analysis of a novel recombinant Mink Enteritis Virus isolated in China - YU, TIANFEI; SUN, CHEN; LI, MING (The Indian Journal of Animal Sciences, 2023)
The primary objective of this study was to detect the presence of MEV in mink samples and investigate the genetic characteristics of the virus. In 2017, a newly identified strain of MEV, named MEV-HLJ, was isolated. The virus’s complete NS1 and VP1 gene sequences were amplified using PCR and subjected to phylogenetic analysis. The results indicated that despite moderate virulence, MEV- HLJ belonged to the attenuated group. Recombination analysis using the GARD programme identified a putative recombination breakpoint at nucleotide position 2,075 between the NS1 and VP1 genes. Separate phylogenetic trees were constructed to confirm the recombinant event. This study provides insights into the genetic diversity and evolution of MEV isolates.